Kinetics of water absorption during rice soaking: a review - Muchlisyiyah, Jhauharotul; Shamsudin, Rosnah; Hashim, Norhashila; Kadir, Roseliza; Che Man, Hasfalina (HH Publisher, 2023)
Glutinous rice (Oryza sativa var glutinosa) is a rice cultivar with a low amylose content (1-2%). Its cultivation is less extensive than that of non-glutinous rice. Most consumption of glutinous rice is for traditional purposes. Hydration is a crucial step in the processing of glutinous rice. It occurs prior to the cooking operation. It is understood that soaking techniques require mass transfer parameters of water diffusion into the rice grain. However, due to the complexity of the soaking process, many features are still completely known. Consequently, it is important to study the physical changes in rice quality during soaking. Several empirical and semi-empirical models of the soaking process are discussed in this paper. For a more efficient soaking procedure, the behaviour of the hydration kinetics and the mathematical modelling of the quality changes during soaking are critical. In addition, the present limitations and probable future scope of study in this field are discussed.